Outlook for a new Asia and Japan's response : a report ([s.n.] [S.l.], 1994)
Seeks to answer questions such as - What exactly is Asia? Where is it going in terms of its value orientations, geography , and roles to be played in the global community? What role should Japan play in its development?
DC